Associations Between Video Game Engagement and ADHD Symptoms in Early Adolescence. Issue 10 (August 2022) - Tiraboschi, Gabriel Arantes; West, Greg L.; Boers, Elroy; Bohbot, Veronique D.; Fitzpatrick, Caroline
Objective: We aim to investigate the direction of causality of the association between adolescent video game playing and later development of ADHD symptoms using a population-based sample of Canadian Youth. Method: The present study is based on longitudinal cohort data ( N = 1, 467). Youth self-reported weekly hours of video game playing as well as ADHD symptoms at both 12 and 13 years of age. Results: Cross-lagged panel model were estimated to examine how adolescent video game playing prospectively contributes to ADHD symptoms while simultaneously considering how adolescent ADHD symptoms may prospectively contribute to videogame playing. Analyses revealed a significant positive association between adolescent video games playing at age 12 and ADHD symptoms at age 13. Youth ADHD symptoms at age 12 did not predict video game use at age 13. Conclusion: Our results help clarify the direction of causality of the association between video game playing and ADHD symptoms and provide evidence that video game playing can represent a risk factor for the development of attention problems in early adolescence.